Benchmarking a novel inorganic scintillation detector for applications in radiation therapy. (December 2019) - Alharbi, Majed; Martyn, Michael; O'Keeffe, Sinead; Therriault-Proulx, François; Beaulieu, Luc; Foley, Mark
Highlights: The hyperspectral approach is used to accurately account for the stem effect. Cerenkov radiation contribution is quantified at various irradiation geometries. Band-pass filters reduced the Cerenkov contribution to a negligible level. Other scintillation mechanisms are affecting the inorganic detector signal. Abstract: Purpose: The aim of this study was to investigate the contribution of Cerenkov radiation to the overall signal measured with a novel inorganic scintillating detector (ISD). Methods: An ISD based on terbium doped gadolinium oxysulphide (Gd2 O2 S:Tb) was used. A hyperspectral technique separated the Cerenkov signal from the radioluminescence (RL) signal of the ISD. The relative contribution of Cerenkov radiation was evaluated under different conditions. The efficiency of using simple spectral correction to reduce the Cerenkov contribution was quantified. Other experiments investigated were the dose-per-pulse dependence observed in our previous study and the absorbed-dose energy dependence when acquiring percentage depth dose curves using Monte Carlo (MC) simulations. Results: The maximum relative contribution of Cerenkov radiation was 2.10% for a 10 × 10 cm 2 field at 10 cm depth. However, this percentage increased to 24% when the ISD was 7 cm out of field and exposed to a 10 × 10 cm 2 field. Using 15 nm and 5 nm band-pass filters reduced the Cerenkov contribution across all experimental conditions by a maximum of 75% and 82%, respectively. The MC simulation results show discrepancies between the measured and simulated PDD profiles using the Gd2 O2 S:Tb scintillator at depth. Conclusion: This study showed that while Gd2 O2 S:Tb ISD provides high-signal intensity, the contribution of Cerenkov radiation under specific conditions can be significant. However, narrow band-pass filters can reduce the Cerenkov signal to a negligible level. The MC simulations suggest mechanisms other than the stem effect and the absorbed-dose energy dependence influence the response of the Gd2 O2 S:Tb scintillator measurements at depth.